Company value: the influence of intellectual capital, growth opportunity, and dividend policy - Suzan, Leny; Syamsudin, Shenny (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aimed to investigate the causes of the decline in stock prices during the COVID-19 pandemic, which can be analyzed based on intellectual capital, growth opportunity, and dividend policies. Therefore, this research focuses on how these variables can influence company value of manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2018 to 2022. Data from 10 companies were analyzed. The simultaneous analysis shows that intellectual capital, growth opportunities, and dividend policy collectively impact company value. In this study, the value of F-statistic is 0.001687, meaning there is a very small probability (less than 0.17%) that the observed results happened by chance. The coefficient of determination indicates that these three variables explain 23.12% of the variation in company value during the study period, while 76.88% is influenced by unexamined factors. Upon closer examination (partial analysis), it is evident that only growth opportunities significantly contribute positively to company value. In contrast, intellectual capital does not demonstrate a positive effect, and dividend policy does not exert a significant negative influence on manufacturing companies in the food and beverage sub-sector listed on the indonesia stock exchange from 2018 to 2022.